Lassiter ebook - Ward, J.R (Black Dagger Brotherhood, 2023)
Destiny, duty, and desire clash in this epic new novel in J.R. Ward's #1 New York Times bestselling Black Dagger Brotherhood series. Lassiter, the fallen angel, is too good at the savior business. In his new role overseeing the fates of all vampires, he's influenced outcomes he shouldn't have—so the Creator is calling him home. But the angel has a reason to stay in Caldwell. He's bonded with a mysterious female who seemed to appear from out of nowhere...and has powers that defy all reason. Rahvyn is well aware that she doesn't belong in the present. And she never intended to stay, for her true place is in the past. Lassiter proves to be undeniable, however, and she lets herself fall for the angel—until a secret he's been keeping comes out and she fears that for him, it's not about love, but duty. As the Omega's son reestablishes the Lessening Society, and the Brotherhood must resume the deadly war, an unfathomable tragedy occurs. In the aftermath, Rahvyn has to decide whether to stay and help—or save herself from an immortal heartbreak she knows will crush her very soul...